Biomechanical study athletes` movement techniques in the hurdles (on example of phase of flight) - Adashevskiy, V. M.; Iermakov, S. S.; Korzh, N. V.; Radoslaw, M.; Prusik, K.; Cieslicka, M. (Physical Education of Students, 2014)
Purpose: To design a theoretical biomechanical model of athletes` movement techniques in the hurdles and then check there movements on real athletes. Material : In the practical part of the study participated 10 smortsmen. Results : Showing the possibility of constructing a theoretical model of hurdling technique. The basis of constructing a model using the known approaches in theoretical mechanics. Shows the calculated and actual performance movement of the athlete. Conclusions : The developed model provides a good theoretical understanding of the interactions of individual elements of movement and the ability to simulate different situations and to determine the optimal values of the kinematic and dynamic characteristics of the movement of the athlete. The model allows the individual elements of motion correction directly in the process of training. When analyzing art movement should consider specific features of physical development and anthropometric characteristics of the athlete's body.